Implementaasi Model Prototype Pada Sistem Informasi Management Pelanggan Di (PT Dharmajaya) - Muhamad Mas`ud; Nurjaya (CV. Multi Kreasi Media, 2023)
Management is a process of planning, organizing, coordinating, and supervising/controlling existing resources in order to achieve goals effectively and efficiently. Management information is closely related to the processing of information sources in the form of data. Because good management information processing will improve the process of delivering information effectively and efficiently. In this study, the implementation of the system uses a prototype model. Until now at PT Dharmajaya, researchers have noticed that many transaction processes carried out are still very conventional, both in terms of recording new customer data, customer transactions to the payment limit notification process. There are so many risks faced by PT Dharmajaya, both in terms of storing customer data, transactions and payments that are still done manually. With this, the researcher aims to design a management information system that is integrated in a computerized way so that all data can be connected to each other into a website at PT Dharmajaya. With the design of this management information system, it is expected to simplify the transaction administration process for customers in the future.